(untitled) (Research, Society and Development, 2021)
Ekbom syndrome leads patients to have a persistent, delusional idea that worms and microbes infest it. This article is a systematic literature review, in which the following platforms were used as a database for the research: PubMed, Lilacs, Cochrane Library and Scientific Electronic Library On-line (SciELO). Case reports published in the period 2017-2021, in Portuguese and English, which addressed the medications used in the treatment of Ekbom syndrome, were used. A bibliographic analysis was carried out by carefully reading the articles based on the aforementioned inclusion and exclusion criteria. Of the 79 results obtained, only 11 addressed the research topic in a clear and objective manner, being used in the preparation of the article. Thus, the main psychiatric disorders associated with the development of the syndrome include: depression, schizophrenia, and anxiety, and dementia caused by levy bodies was also reported as a possible trigger of the disease, in addition, the prevalence of Ekbom’s Syndrome it is higher in women aged 50-60 years. With this, it became noticeable that Ekbom syndrome is a disease predictive of prevalence in society, and that, due to its unknown pathophysiology, it needs further research on the subject.